2019
DOI: 10.1155/2019/1418456
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Biochemical, and Climatological Analysis of Three Moroccan Henna Verities

Abstract: In this study, we aimed to evaluate planted Henna in three sites in Morocco, namely, Alnif, Tafraoute Sidi Ali, and Tazzarine. Morphometric study shows that Tafraoute Sidi Ali Henna variety has highest geometric and weight parameters (length of 27.48 mm, width of 10.92 mm, specific mass of 25.1 mg/leaf, leaf area of 51, 53 mm2, and rib’s number of 9.41) when compared to Alnif and Tazzarine varieties. On the other hand, biochemical analysis shows that Tazzarine Henna variety, in the first rank, is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The protective effect of our formulated treatments on burned skin is directly related to their lipid content. This has been revealed by El Massoudi et al, who showed that the extracts of L. inermis leaves are very rich in total lipids [39].…”
Section: Average Surface and Mean Percentage Of Burn Contractionmentioning
confidence: 71%
See 1 more Smart Citation
“…The protective effect of our formulated treatments on burned skin is directly related to their lipid content. This has been revealed by El Massoudi et al, who showed that the extracts of L. inermis leaves are very rich in total lipids [39].…”
Section: Average Surface and Mean Percentage Of Burn Contractionmentioning
confidence: 71%
“…A study revealed that the healing effect of these natural blends is due to mechanisms such as cell multiplication, activation of collagen synthesis, antioxidant power and antimicrobial and anti-inflammatory effects [38]. In the case of L. inermis, its richness in bioactive molecules such as fatty acids, triglycerides, saponins, tannins, flavonoids, polyphenols and others [39,40] has been observed. These compounds contain a hydroxyl function that allows them to trap free radicals, giving them significant antioxidant power.…”
Section: Average Surface and Mean Percentage Of Burn Contractionmentioning
confidence: 99%
“…27 The methanolic extract of Henna leaves that cultivated in three different sites in Morocco showed the highest flavonoid compounds in Henna cultivated in Alnif at 13.52 g/100 g followed by 8.04 g/100 g Henna from Tafraoute Sidi Ali. The lowest flavonoids compound was found in Henna from Tazzarine at 5.68 g/100 g. 28 A sample of Henna leaves was collected in Elele, Ikwerre L.G.A., Rivers State. The Henna leaves were extracted using two different solvents (N-butanol leaf extract and ethylacetate leaf extract).…”
Section: Flavonoidsmentioning
confidence: 99%
“…The result showed high amounts of gallic acid at 81 mg/100 g DW (26). Soukaina et al 28 conducted a study to evaluate the Henna leaves in three different sites in Morocco which are Alnif, Tafraoute Sidi Ali and Tazzarine. The collected Henna leaves were extracted using methanol.…”
Section: Phenolsmentioning
confidence: 99%
See 1 more Smart Citation